2019 IEEE Conference on Games (CoG) 2019
DOI: 10.1109/cig.2019.8848062
|View full text |Cite
|
Sign up to set email alerts
|

Application of Retrograde Analysis on Fighting Games

Abstract: With the advent of the fighting game AI competition [34], there has been recent interest in two-player fighting games. Monte-Carlo Tree-Search approaches currently dominate the competition, but it is unclear if this is the best approach for all fighting games. In this thesis we study the design of two-player fighting games and the consequences of the game design on the types of AI that should be used for playing the game, as well as formally define the state space that fighting games are based on. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…My previous work focused on an application of AI to fighting games to better understand game balancing and game design (Yu and Sturtevant 2019). The goal of the AI is not to play the game the best, but instead is an AI tool for the developer to be able to identify moves that could be considered over-or under-powered.…”
Section: Previous Workmentioning
confidence: 99%
“…My previous work focused on an application of AI to fighting games to better understand game balancing and game design (Yu and Sturtevant 2019). The goal of the AI is not to play the game the best, but instead is an AI tool for the developer to be able to identify moves that could be considered over-or under-powered.…”
Section: Previous Workmentioning
confidence: 99%
“…This approach has proven effective in fast-paced fighting games where experienced players can reliably predict opponents' moves. Extensions apply hidden Markov models [19] and AI agents [20], [21] to improve fighting game input predictions. However, current methods narrowly focus on one specific genre and may not generalize well to others.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39–41 ] The action at a high level is not well understood, although traditional studies have demonstrated excellent performance in solo maneuvers or progressed to simple navigation scenarios. [ 11,42–44 ]…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] The action at a high level is not well understood, although traditional studies have demonstrated excellent performance in solo maneuvers or progressed to simple navigation scenarios. [11,[42][43][44] Human athletes are required to be highly skilled in four areas: 1) maneuver tactics, 2) human-body control, 3) movement strategy, and 4) navigation etiquette, to be effective. The human…”
mentioning
confidence: 99%